The effects of ECMO on neurological function recovery of critical patients: A double-edged sword - Cai, Jinxia; Abudou, Halidan; Chen, Yuansen; Wang, Haiwang; Wang, Yiping; Li, Wenli; Li, Duo; Niu, Yanxiang; Chen, Xin; Liu, Yanqing; Li, Yongmao; Liu, Ziquan; et al. (Frontiers in Medicine, 2023)
Extracorporeal membrane oxygenation (ECMO) played an important role in the treatment of patients with critical care such as cardiac arrest (CA) and acute respiratory distress syndrome. ECMO is gradually showing its advantages in terms of speed and effectiveness of circulatory support, as it provides adequate cerebral blood flow (CBF) to the patient and ensures the perfusion of organs. ECMO enhances patient survival and improves their neurological prognosis. However, ECMO-related brain complications are also important because of the high risk of death and the associated poor outcomes. We summarized the reported complications related to ECMO for patients with CA, such as north–south syndrome, hypoxic–ischemic brain injury, cerebral ischemia–reperfusion injury, impaired intracranial vascular autoregulation, embolic stroke, intracranial hemorrhage, and brain death. The exact mechanism of ECMO on the role of brain function is unclear. Here we review the pathophysiological mechanisms associated with ECMO in the protection of neurologic function in recent years, as well as the ECMO-related complications in brain and the means to improve it, to provide ideas for the treatment of brain function protection in CA patients.